Maternal cell phone use during pregnancy and child cognition at age 5 years in 3 birth cohorts. (November 2018) - Sudan, Madhuri; Birks, Laura Ellen; Aurrekoetxea, Juan J.; Ferrero, Amparo; Gallastegi, Mara; Guxens, Mònica; Ha, Mina; Lim, Hyungryul; Olsen, Jorn; González-Safont, Llúcia; Vrijheid, Martine; Kheifets, Leeka
Abstract: Background: There have been few studies of children's cognitive development in relation to mothers' cell phone use, and most were limited to outcomes at age 3 years or younger. We examined the relationship between maternal cell phone use during pregnancy and cognitive performance in 5-year old children. Methods: This study included data from 3 birth cohorts: the Danish National Birth Cohort (DNBC) (n = 1209), Spanish Environment and Childhood Project (INMA) (n = 1383), and Korean Mothers and Children's Environment Health Study (MOCEH) (n = 497). All cohorts collected information about maternal cell phone use during pregnancy and cognitive performance in children at age 5. We performed linear regression to compute mean differences (MD) and 95% confidence intervals (CI) in children's general, verbal, and non-verbal cognition scores comparing frequency of maternal prenatal cell phone use with adjustments for numerous potential confounding factors. Models were computed separately for each cohort and using pooled data in meta-analysis. Results: No associations were detected between frequency of prenatal cell phone use and children's cognition scores. Scores tended to be lower in the highest frequency of use category; MD (95% CI) in general cognition scores were 0.78 (−0.76, 2.33) for none, 0.11 (−0.81, 1.03) for medium, and −0.41 (−1.54, 0.73) for high compared to low frequency of use. This pattern was seen across all cognitive dimensions, but the results were imprecise overall. Conclusion: We observed patterns of lower mean cognition scores among children in relation to high frequency maternal prenatal cell phone use. The causal nature and mechanism of this relationship remain unknown. Highlights: Prenatal maternal cell phone use may be related to child cognition. Cognition scores are slightly lower in relation to higher frequency use, although imprecise. The causal mechanisms are unknown at this time. The association is likely affected by social and behavioral factors.